Genotype x environment interaction and stability analysis for yield and its attributes in garlic (Allium sativum L.) - Gupta, R K Singh, B K Dubey, R P (Journal of Spices and Aromatic Crops, 2016)
Genotype environment interaction is very important to the plant breeder in developing improved varieties. The present investigation was carried out at National Horticultural Research and Development Foundation, Karnal to identify the suitable and stable genotypes for Rabi season with higher yield and others horticultural attributes. It is concluded from present investigation that the genotype G-384, G-324, G-378, G-376 and check YamunaSafed-3 (G-282) performed well in favorable environment for gross as well as marketable yield and considered as most stable and responsive genotype as it possesses higher yield along with the bi=one or near one and nonsignificant S2di values and hence could be recommended for adoptability. These above genotypes can be further exploited in breeding programme for increasing the production of garlic.